2001
DOI: 10.1093/ije/30.1.60
|View full text |Cite
|
Sign up to set email alerts
|

Lowered weight gain during pregnancy and risk of neural tube defects among offspring

Abstract: We did not have information on weight gain during early pregnancy. Because weight gain during the relevant embryological period for NTD (first month post-conception) is relatively small and often variable, it seems less likely that elevated NTD risks indicate a causal association between lowered weight gain throughout pregnancy and abnormal development of the neural tube. It seems more likely that lowered weight gain is a consequence of carrying an NTD-affected fetus. However, what this consequence is and why … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 25 publications
0
20
0
Order By: Relevance
“…Data from a previous population-based case-control study in California, conducted prior to mandatory food folic acid fortification in the U.S., suggested an association between NTDs and lower maternal weight gain, with an OR of 3.6 (95% CI 2.7, 4.7) for average weight gain <0.27 kg/week compared to 0.27–0.52 kg/week (Shaw and others, 2001). The association was greater for anencephaly than for spina bifida.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Data from a previous population-based case-control study in California, conducted prior to mandatory food folic acid fortification in the U.S., suggested an association between NTDs and lower maternal weight gain, with an OR of 3.6 (95% CI 2.7, 4.7) for average weight gain <0.27 kg/week compared to 0.27–0.52 kg/week (Shaw and others, 2001). The association was greater for anencephaly than for spina bifida.…”
Section: Discussionmentioning
confidence: 99%
“…All analyses were stratified by maternal gestational age (< 37 vs. ≥ 37 weeks) given the inherent association of weight gain with duration of gestation and the preponderance of preterm deliveries among the case groups. Multivariable logistic regression analyses were conducted to examine the association of weight gain during pregnancy (described above) with specific phenotypes adjusting for potential confounders which were selected a priori based on previously demonstrated associations with weight gain or the phenotypes under study (Abrams and others, 1995; Carmichael and others, 2003; Feldkamp and others, 2011; Mac Bird and others, 2009; Shaw and others, 2001). The covariates for NTDs were race/ethnicity (non-Hispanic white, non-Hispanic black, Hispanic, other), education (< 12, 12, > 12 years), maternal pre-pregnancy BMI (< 18.5, 18.5–24.9, 25.0–29.9, ≥ 30 kg/m 2 ), use of folic acid-containing supplements (any versus none) during the month before and the first three months of pregnancy, maternal total energy intake (kcal/day), and dietary folate intake (dietary folate equivalents, µg/day).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, folic acid intake has been linked with neural tube closure, 83 and low gestational weight gain appears to be associated with higher risk of neural tube deficits. 84 Excessive gestational weight gain, on the other hand, puts women at risk for hypertension. 85 Regular exercise (three to four times per week) appears to be important for fetal development.…”
Section: Negative Health Behaviorsmentioning
confidence: 99%
“…Elevated risk of delivering offspring with NTDs following intrauterine famine exposure has been observed [76]. Several studies revealed also an increased risk for delivering infants with NTDs in association with lowered gestational maternal weight gain [77,78]. The UNICEF reported that the availability of calories in the food ration of Iraqi population was equivalent to 1093 calories/person (approximately 40% of daily requirement) for the period 1990–1997 which increased then to 2030 and lastly to 2475 in 2002 [79].…”
Section: Introductionmentioning
confidence: 99%